2014
DOI: 10.1007/978-4-431-55209-3_2
|View full text |Cite
|
Sign up to set email alerts
|

Benefits of Generalised Microsimulation

Abstract: This paper states our position regarding the desirable properties of a discrete simulation environment and details our response to this. Following a brief introductory examination of the pre-existing art in microsimulation modelling, we describe our approach and detail its structure and use.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…The world is modelled using cells and peeps; cells are abstract locations and peeps are abstract entities within those locations. Further details can be found in our previous publications Piper et al, 2010); a more complete description of Simulacron can be found in Keep (2012).…”
Section: Introductionmentioning
confidence: 99%
“…The world is modelled using cells and peeps; cells are abstract locations and peeps are abstract entities within those locations. Further details can be found in our previous publications Piper et al, 2010); a more complete description of Simulacron can be found in Keep (2012).…”
Section: Introductionmentioning
confidence: 99%
“…In this paper we present development of our microsimulation framework, Simulacron, (Keep, 2012) to multiinfections with a preliminary investigation into the building of a model for studying the impact of multiple biological weapons releases on a population. In the work reported here we have used plague and smallpox as two indicative and plausible (Gordon, 2007) biological weapons.…”
Section: Introductionmentioning
confidence: 99%